Assaying multiple 125I seeds with the well-ionization chamber SourceCheck4π 33005 and a new insert - Candela-Juan, Cristian; Ballester, Facundo; Perez-Calatayud, Jose; Vijande, Javier (Journal of Contemporary Brachytherapy, 2015)
Purpose: To provide a practical solution that can be adopted in clinical routine to fulfill the AAPM-ESTRO recommendations regarding quality assurance of seeds used in prostate permanent brachytherapy. The aim is to design a new insert for the well-ionization chamber SourceCheck 4π 33005 (PTW, Germany) that allows evaluating the mean air-kerma strength of up to ten 125 I seeds with one single measurement instead of measuring each seed individually. Material and methods: The material required is: a) the SourceCheck 4π 33005 well-ionization chamber provided with a PTW insert to measure the air-kerma strength SK of one single seed at a time; b) a newly designed insert that accommodates ten seeds in one column, which allows measuring the mean SK of the ten seeds in one single measurement; and c) a container with ten seeds from the same batch and class of the seeds used for the patient implant, and a set of nine non-radioactive seeds .The new insert is characterized by determining its calibration coefficient, used to convert the reading of the well-chamber when ten seeds are measured to their mean SK. The proposed method is validated by comparing the mean SK of the ten seeds obtained from the new insert with the individual measurement of SK of each seed, evaluated with the PTW insert. Results : The ratio between the calibration coefficient of the new insert and the calibration coefficient of the PTW insert for the SourceCheck 4π 33005 is 1.135 ± 0.007 (k = 1). The mean SK of a set of ten seeds evaluated with this new system is in agreement with the mean value obtained from measuring independently the SK of each seed. Conclusions : The new insert and procedure allow evaluating the mean SK of ten seeds prior to the implant in a single measurement. The method is faster and more efficient from radiation protection point of view than measuring the individual SK of each seed.